Leadership And Organizational Culture In The Departement Of Transportation Badung Regency - Sugiartha, Komang Agus; Yuesti, Anik; Sudja, I Nengah (The journal of contemporary issues in business and government, 2021)
Servant leadership is a leadership model that places service to others, including employees, customers and society as a top priority. Servant Leadership emphasizes increased service to others, a holistic approach to work, a sense of community and shared decision-making power. Organizational culture is the values, principles, traditions, and attitudes that influence the way organizational members act. Job satisfaction is a feeling of satisfaction or dissatisfaction with employees at work. Employees who are satisfied with their work are happy to do their jobs and always try to improve their abilities and skills. Respondents in this study were employees at the Department of Transportation, Badung Regency. The number of respondents in this study were 76 respondents, the sampling technique used a probability sample using the proportional stratified random sampling method. This technique is a sampling technique that provides equal opportunities for each member of the population at each level (in this case the number of employees in each field) to be selected as a sample. This study uses multivariate analysis using a structural equation model or SEM (Structural Equation Model) with a variance-based or component-based approach called PLS (Partial Least Square). The results of this study indicate that: 1) servant leadership directly has a positive and significant effect on job satisfaction, 2) organizational culture directly has a positive and significant effect on job satisfaction, 3) servant leadership directly has a positive and significant effect on employee performance, 4) organizational culture does not have a positive and significant effect on employee performance, 5) job satisfaction has a positive and significant effect on employee performance, 6) job satisfaction is partially mediated directly or indirectly, servant leadership on employee performance, 7) Job satisfaction is non-mediated indirectly. Direct organizational culture on employee performance proved to be insignificant.